Antimicrobial resistance profile of Enterococcus species and molecular characterization of Vancomycin resistant Enterococcus faecium from the fecal samples of newly diagnosed adult HIV patients in Dar es Salaam, Tanzania - Kibwana, Upendo O.; Manyahi, Joel; Moyo, Sabrina J.; Blomberg, Bjørn; Roberts, Adam P.; Langeland, Nina; Mshana, Stephen E. (Frontiers in Tropical Diseases, 2024)
Background: Enterococci are becoming clinically more important especially among immunocompromised patients. Of concern are vancomycin resistant enterococci (VRE) which have both intrinsic and acquired forms of resistance. This work aimed to determine the antimicrobial resistance patterns of Enterococcus spp. and characterize VRE isolate obtained from HIV-infected patient using whole genome sequencing (WGS).Antimicrobial susceptibility testing was done on 57 enterococci isolates by both the disk diffusion method and Epsilometer test (E-Test). WGS was performed on VRE isolate determined by E-test.Results: Out of the 57 enterococci isolates; 58% (33/57) were E. faecalis, 39% (22/57) E. faecium and 4% (2/57) were E. gallinarum. The highest antimicrobial resistance was observed in E. faecalis isolates. The most prevalent antimicrobial resistance was observed towards quinupristindalfopristin (56%, 32/57), followed by ciprofloxacin (28%), tigecycline (18%), daptomycin (16%), chloramphenicol (14%), ampicillin and teicoplanin (2%). Multidrug resistance (MDR) was detected in 11% (6/57) of the isolates. Vancomycin resistance and high-level gentamycin resistance (HLGR) were observed in one E. faecium and one E. faecalis isolates respectively. The VRE was typed as ST80, carried vanA and other resistance genes for aminoglycosides, tetracyclines, quinolones and ampicillin. Furthermore, the isolate had chromosomal mutations responsible for quinolone (gyrA (p.S83I) and parC (p.S80I) and ampicillin (pbp5) resistance.The detection of VRE, HLGR and MDR in the study settings underscores the sustained surveillance of VRE in high-risk groups and institution of infection control measures for prompt identification and isolation of carriers to prevent the spread of VRE in the community and hospital settings.